Increased natural killer cell subsets with inhibitory cytokines and inhibitory surface receptors in patients with recurrent miscarriage and decreased or normal subsets in kidney transplant recipients late post-transplant. (31st May 2018) - Zhu, L; Aly, M; Wang, H; Karakizlis, H; Weimer, R; Morath, C; Kuon, R J; Toth, B; Ekpoom, N; Opelz, G; Daniel, V
Summary: Patients with recurrent miscarriage (RM) show up-regulated cytotoxic natural killer (NK) cells that are suspected to play a causal role in abortion. In the present study, we investigated counter-regulating inhibitory mechanisms and compared the results in RM patients with those of healthy controls (HC), patients with end-stage renal disease (ESRD) and kidney transplant recipients late post-transplant (TX). NK, NK T and T cell subsets were analysed in the peripheral blood of 31 RM, 14 female ESRD and nine female TX patients as well as 21 female HC using eight-colour fluorescence flow cytometry. Compared with HC, RM patients showed significantly higher absolute numbers of CD56 + NK cells co-expressing the phenotype interferon (IFN)-γR +, IL-4 +, transforming growth factor (TGF)-β +, IL-4 + human leucocyte antigen D-related (HLA-DR) +, TGF-β + HLA-DR +, IL-4 + TGF-β +, IL-4 + TGF-β −, IFN-γ + and/or IL-10 − IFN-γ + (all P ≤ 0·01), more IL-17 + CD56 bright ( P = 0·028) NK cells and more CD56 dim CD16 + NK cells co-expressing IFN-γR, IFN-γ, IL-4 and/or TGF-β (all P ≤ 0·01). When the same cell subsets were analysed in ESRD or TX patients, cytokine-producing NK cell subsets were not significantly different from those of HC. RM patients showed significantly higher absolute numbers of CD158a +, CD158b +, CD158a − CD158e + (all P < 0·05), NKG2D + NKG2A +, NKG2D + NKG2A −, NKG2D + and/or NKG2A + (all P ≤ 0·01) CD56 + NK cells and higher CD158a +, CD158b + (all P < 0·05), NKG2D + and/or NKG2A + (all P < 0·01) CD56 dim+ CD16 + NK cells than HC. In contrast, ESRD patients had normal and TX recipients had lower CD158a + and NKG2D + NKG2A − CD56 + NK cells and lower CD158a + CD56 dim+ CD16 + NK cells (all P < 0·05) than HC. RM patients have abnormally high circulating NK cells expressing inhibitory cytokines and inhibitory surface receptors which might contribute to the pathogenesis of RM. Graphical Abstract: